Elaborating the Human Aspect of the NIST Framework for Cyber-Physical Systems. (September 2018) - Burns, Martin; Manganelli, Joe; Wollman, David; Laurids Boring, Ronald; Gilbert, Stephen; Griffor, Edward; Lee, Yi-Ching; Nathan-Roberts, Dan; Smith-Jackson, Tonya
The National Institute of Standards and Technology (NIST) has developed a Framework for Cyber-Physical Systems (CPS Framework) that supports system engineering analysis, design, development, operation, validation and assurance of CPS. Cyber-physical systems (CPS) comprise interacting digital, analog, physical, and human components engineered for function through integrated physics and logic. For instance, a city implementing an advanced traffic management system including real-time predictive analytics and adaptation/optimization must consider all aspects of such a CPS system of systems' functioning and integrations with other systems, including interactions with humans. One Aspect (or grouping of stakeholder concerns) of the CPS Framework is the Human Aspect . NIST is engaging HFES in a panel discussion to elaborate Human Aspect concerns, such as constructs, measures, methods, and tools.